2019
DOI: 10.4103/sjg.sjg_547_18
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the optimal volume of ascitic fluid for the precise diagnosis of malignant ascites

Abstract: Background/Aims:The aim of this study was to determine the optimal volume of peritoneal effusion required to diagnose malignant ascites.Patients and Methods:The authors recruited 123 patients with shifting dullness and obtained 123 peritoneocentesis fluid samples. The samples were divided into seven aliquots of 10, 50, 100, 150, 200, 250, and 300 mL for cytopathological examination. The sensitivity, specificity, negative predictive value (NPV), and positive predictive value (PPV) were calculated for each aliqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Zhang et al, in their study of 123 ascitic fluid patients, reported a cutoff value of 200 mL [31], while Rooper et al, with a cohort of 2665 patients with ascites, proposed a volume of 80 mL [32]. For pericardial effusions, Rooper et al have considered 60 mL as optimal [33], while Dragoescu et al, with a cohort of 128 pericardial effusion patients, with a mean volume of 60 mL and a malignancy rate of 24.2%, did not find an optimal volume [34].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al, in their study of 123 ascitic fluid patients, reported a cutoff value of 200 mL [31], while Rooper et al, with a cohort of 2665 patients with ascites, proposed a volume of 80 mL [32]. For pericardial effusions, Rooper et al have considered 60 mL as optimal [33], while Dragoescu et al, with a cohort of 128 pericardial effusion patients, with a mean volume of 60 mL and a malignancy rate of 24.2%, did not find an optimal volume [34].…”
Section: Discussionmentioning
confidence: 99%
“…No clear‐cut guidelines exist in the current system recommending the minimum volume of sample required for labelling it as NFM. A study conducted by Zhang et al for the determination of the optimal volume of ascitic fluid in the precise diagnosis of malignant ascites concluded that the sensitivity for the diagnosis of malignant ascites is closely related to the volume of peritoneal fluid that is extracted by peritoneocentesis 27 …”
Section: Discussionmentioning
confidence: 99%
“…It is of clinical interest in determining the standards for adequate sampling. Previous correlational studies have proposed cutoffs of 80-200 mL for volume adequacy [1][2][3]. This recommendation may not be always practical where patient and disease factors limit fluid volume and may not apply to specimens collected or divided in consecutive aliquots.…”
Section: Introductionmentioning
confidence: 99%